Synthesis of Heterocyclic Compounds Derived from 2-Mercapto Quinoline - Sharba, A. H.; Hassan, H. A.; Hassan, D. F. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
2-Mercapto quinoline was used as precursor for synthesis of new heterocyclic derivatives of quinoline nucleus such as pyrazole (3), pyrazolone (4), 1,3,4-oxadiazole (5) and 1,2,4-triazole (8). New Schiff bases (9a-e) were obtained from the reaction of hydrazide derivative (2) with miscellaneous aldehydes and ketones. All synthesized compounds were characterized by physical and spectral data.